UV radiation below an Arctic vortex with severe ozone depletion - Knudsen, B. M.; Jønch-Sørensen, H.; Eriksen, P.; Johnsen, B. J.; Bodeker, G. E. (CCSD, 2005)
International audience The erythemally weighted (UV) irradiance below the severely depleted Arctic vortices in spring 1996 and 1997 were substantially elevated. On average the UV increased 36 and 33% relative to the 1979-1981 mean assuming clear skies from day 80-100 in 1996 and 1997, respectively. On clear sky days large regions of the Arctic experienced maximum UV increases exceeding 70 and 50% on single days in 1996 and 1997, respectively. A minor fraction of these increases are not anthropogenic and have a dynamical origin as seen by comparison to 1982, when hardly any ozone depletion is expected.